The Roles of Land Information Systems (LIS) and Geodetic Spatial Reference Frames In Property Taxation and Revenue Drive in Rivers State: A Case Study of Portharcourt Cadastre - Leonard Michael Onyinyechi Aminigbo; Lawrence Hart (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Land management is becoming more recognized as a community-wide if not global need. Landed assets are an important source of government revenue in Rivers state, and they necessitate a land information systems infrastructure. The creation of LIS of Port Harcourt property layouts is critical to realizing that ambition. Results of this research paper has lots of potential in providing sustainable land relationships and information to decision makers (land administrators and revenue drivers) in Rivers state so that they can make decisions that are beneficial to sustainable development in the context of efficient land administration and management. This study used geospatial methodologies to document, create, and populate land information in Trans-Amadi and GRA phases 1 and 2 of Port Harcourt's cadastral layouts. According to the findings of this study's analysis, discussions, and queries, effective usage of the LIS, which is driven by many aspects of services supplied by government Ministries, Departments, and Agencies, will increase efficiency and productivity in property taxation in capital city of Port Harcourt.The following recommendations were made as a result of this research: Information decentralization to make it easier to keep track of and recollect data. Fees charged for various services given are published and displayed. Official procedures should be simplified, and a faster and more efficient method of moving files should be established. In Rivers state, there has been a reduction in the time it takes to complete title paperwork for landed properties. All occupants of government lands in Port Harcourt will get a formal allocation of encroached lands and a certificate of title. A chart for employee training, particularly in ICT, should be prepared. External consultants should be taught customer service, change management, time management, project management, supervisory management, and systems administration. The state's Ministry of Lands and Survey should develop a website that enables for e-payment of grand rents, C of O applications, and land mapping. Finally, the LIS of cadastral layouts in Port Harcourt as a pilot project should be implemented in major towns and cities across the LGAs of Rivers state for efficient land administration, property taxation, and revenue generation, in line with the Federal Government of Nigeria's current land reform programme. Keyword: Taxation, information, land, systems, cadastre, and revenue are some of the key phrases.